Cycloaddition of CS2 to N‐benzylaziridine to synthesize N‐benzylthiazolidine‐2‐thione: a novel reaction route proposed by DFT Study. (13th May 2016) - Singh, Amritpal; Goel, Neetu
Abstract: N‐Benzylthiazolidine‐2‐thione is the keyintermediate for the synthesis of pharmaceutically important compounds. A novel route for the synthesis of N‐benzylthiazolidine‐2‐thione throughcycloaddition of CS2 with N‐benzylaziridine in the presence of 1, 3‐di‐tert‐butylimidazolium‐2‐dithocarboxylate (catalyst I ) has been proposed by reliable computations performed within the formalism of density functional theory. The mechanism of the proposed reaction is similar to thecycloaddition of tertiary aziridines andcarbon dioxide using a recyclable catalyst that is reported to provide access to 3‐substituted 2‐oxazolidones with excellent yield. Because the rate determining step needs to surmount a high energy barrier, the reaction route has been deciphered in high boiling solvent (1, 2‐ethanediol). The highlight of the mechanistic route detailed here is that the proposed pathway is a cyclic process that is exothermic in nature with the regeneration of the catalyst and involves simple reagents. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The step by step reaction pathway presents the details of the proposed novel route to pharmaceutically important N‐benzylthiazolidine‐2‐thione through coupling of CS2 with N‐benzylaziridine using DFT formalism. Keeping in view the impediments of the limited synthetic route to N‐benzylthiazolidine‐2‐thione, theoretical prediction of synthesizing N‐benzylthiazolidine‐2‐thione through cycloaddition of CS2 with N‐benzylaziridine would encourage synthetic chemists to follow the proposed route to an important intermediate in various reactions of pharmaceutical importance.